2005
DOI: 10.1210/en.2005-0380
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Infusion of Interleukin-1β and Chorionic Gonadotropin Induces Endometrial Changes that Mimic Early Pregnancy Events in the Baboon

Abstract: Both human chorionic gonadotropin (hCG) and IL-1beta induce changes in the endometrium that are associated with the establishment of pregnancy. We investigated the synergistic effect of these two embryonic signals on endometrial function using a baboon model of simulated pregnancy. Recombinant hCG (30 IU/d) was infused between d 6 and 10 post ovulation (PO) to mimic blastocyst transit. On the expected day of implantation (d 10 PO), IL-1beta (12 ng/d) or IL-1 receptor antagonist (IL-1Ra; 12 ng/d) was infused fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 46 publications
4
60
0
1
Order By: Relevance
“…Studies from our laboratory indicate that the primary effect of (h)CG on stromal fibroblasts is the induction of αSMA, which is a consequence of integrins on the stromal cell membrane binding to secreted extracellular matrix proteins [16,[62][63][64]. We have demonstrated that the induction of αSMA by (h)CG may be essential in order to decrease the progesterone-regulated proliferation in these cells, and consequently initiating differentiation and a qualification to inhibit stromal cell apoptosis [65].…”
Section: Role Of the Cytoskeletonmentioning
confidence: 89%
“…Studies from our laboratory indicate that the primary effect of (h)CG on stromal fibroblasts is the induction of αSMA, which is a consequence of integrins on the stromal cell membrane binding to secreted extracellular matrix proteins [16,[62][63][64]. We have demonstrated that the induction of αSMA by (h)CG may be essential in order to decrease the progesterone-regulated proliferation in these cells, and consequently initiating differentiation and a qualification to inhibit stromal cell apoptosis [65].…”
Section: Role Of the Cytoskeletonmentioning
confidence: 89%
“…It is, thus, possible that a defective NALP7 leads to abnormal oocyte maturation and growth and subsequently abnormal establishment of maternal methylation marks on imprinted genes. NALP7 is also known to regulate IL-1, a pleiotropic cytokine that activates a number of inflammatory pathways required for blastocyst implantation and throughout gestation (McMaster et al 1993;Rivier and Vale 1990;Strakova et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, dans un modèle de primate non humain, l'infusion d'hCG et d'IL1 mime les changements caractéristiques qui interviennent lors d'une grossesse et conduit à l'immunotrophisme (voir note 2) [39]. Dans un modèle murin, certaines expériences ont suggéré que l'injection du récepteur antagoniste de l'IL1, IL1Ra, réduisait considérable-ment le nombre d'embryons qui s'implantent en altérant la réceptivité de l'endomètre.…”
Section: Dernières Avancéesunclassified